PENGUATAN JEJARING SOSIAL MELALUI MEDIA SOSIAL DAN PELATIHAN LINGUISTIK DALAM MENINGKATKAN LITERASI DIGITAL DAN EKONOMI KREATIF BAGI KELOMPOK PEREMPUAN - Cahyadi Saputra Akasse; Dwi Ratnasari; Andi Subhan (Jurnal Pengabdian Masyarakat Multidisiplin, 2026)
Low digital literacy and limited linguistic capacity constitute significant barriers for the Literacy-Savvy Housewives Forum in Dutohe Village to participate in socio-economic empowerment initiatives. This Community Service Program (PKM) aims to enhance digital literacy capacity and strengthen social networking through linguistic training for this group of women. The program involved 23 respondents who were active members of the forum. The implementation was conducted through eight structured stages, including team formation, needs assessment, problem identification and solution design, preparation, and implementation of training and mentoring activities, and evaluation. The results demonstrated a significant improvement in participants' capacity, as the mean score increased from 53.13 (pre-test) to 69.70 (post-test), indicating a mean gain of 16.56 points. Participants were now able to utilize social media more effectively for promoting creative economy products and demonstrated more persuasive communication skills in developing product narratives. It is recommended that more personalized and intensive follow-up mentoring should be provided to optimize the application of digital technical skills and ensure consistency in the quality of product description writing among all members.